Analisis Sebaran Banjir Akibat Keruntuhan Bendungan Bulango Ulu Kabupaten Bone Bolango: Analysis of Flood Distribution Due To The Collapse of The Bulango Ulu Dam, Bone Bolango Regency - Fatmawati Abdul Razak, Fatma; Alitu, Aryati; Labdul, Barry Yusuf (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2024)
The dam is one of the important water resource infrastructure buildings and provides benefits to the local community. In addition to the many benefits, dams can also pose great risks. In Permen PU No. 27 of 2015 concerning dams, the definition of dam failure is the partial or complete collapse of the dam or its complementary buildings and/or damage that results in the malfunctioning of the dam. Dam collapses can cause major flooding in the lower reaches of the dam. The devastating disaster does not only occur on the site around the building, but covers a large area downstream of the dam and can also cause huge losses that can threaten human life with material losses as well as human souls. Modeling of flood inundation due to dam collapse was carried out with HEC-RAS v6.0 with the help of ArcGIS v10.3 with the cause of the dam collapse being due to overtopping and piping with a case study of Bolango Ulu Dam located in Bone Bolango Regency. In the overtopping scenario, it was found that flood inundation in Gorontalo City reached 43% of the area of 7959 ha, with a maximum average flood depth of 3.81 m, a maximum average speed of 1.83 m / second and an average flood arrival time of 2.50 hours. In the piping scenario, it was found that flood inundation in Gorontalo City reached 42% of the area of 7959 ha, with a maximum average flood depth of 3.33 m, a maximum average speed of 1.51 m / second and an average flood arrival time of 2.66 hours.